Two-steps synthesis of D-glucaric acid via D-gluconic acid by electrocatalytic oxidation of D-glucose on gold electrode: Influence of operational parameters. (1st April 2021) - Moggia, Giulia; Schalck, Jonathan; Daems, Nick; Breugelmans, Tom
Abstract: Glucose electrooxidation to glucaric acid, a highly valuable platform chemical, has been conducted, for the first time, in two consecutive steps employing a bare gold electrode in a batch reactor. The first step, at low potential, enabled the effective formation of the intermediate, gluconic acid, promoted by the oxidation of the aldehyde group on C1. For this reaction step, except for the reaction time, all the operational parameters had a strong impact on the selectivity. At the optimal conditions of pH 11.3, 5°C and 0.04 M initial glucose, a maximum selectivity of 97.6% was obtained, the highest reported to date for the electrochemical process, with a conversion of 25%. At higher potential, gluconic acid was further converted to glucaric acid by the oxidation of the hydroxymethyl group on C6. For this oxidation step, the variation of the operational parameters (pH, gluconic acid initial concentration, reaction temperature and time) had no conspicuous effect on the selectivity, while the applied potential had a major role: at 1.1 VRHE, a maximum selectivity of 89.5% to glucaric acid was obtained, which is one of the highest values reported in literature so far. In all experiments, irrespective of conditions and reaction time, a maximum concentration of ca 1.2 mM of glucaric acid was achieved, and a drastic decrease of the current density was observed in the first hours of electrolysis. Additional control experiments revealed a poisoning process caused by glucaric acid that, once formed, remains strongly bonded to the catalyst's active sites, thus deactivating it.